“With the Greatest Admiration:” Lessons Learned from Correspondence Among Foundational Leaders in Public Health - Schieferecke, Grace (My University, 2025)
During the late nineteenth century, modern medicine was taking off due to revolutions in scientific discovery. New fields of medicine like bacteriology and sanitation were established, with advancements in these fields leading to an increase in overall life expectancy. Leaders like Dr. John Shaw Billings, Dr. George Miller Sternberg, and Dr. Robert Koch revolutionized medicine by discovering, establishing, and communicating public health practices. With my mentor Dr. Kastner, and fellow students, I visited the National Library of Medicine in Bethesda, Maryland to explore primary documents from these leaders. In our archival research, I found a letter written by Koch to Sternberg, suggesting a positive relationship between the two leaders across the Atlantic. Koch’s communication about infectious diseases and commentary on prevention measures, like city water design, particularly piqued my interest. This letter suggests that Koch was a firm believer in applying the Germ Theory he learned in a lab to the real world. I also included material from Dr. Kastner’s UHP course I took in 2021, detailing two letters showing correspondence between physicians and medical officers between countries. This collaboration serves as a model for how public health practices should and do often look today. With Dr. Kastner, I plan to publish the results of this project in K-State's One Health newsletter and submit it for my honors project.